2015
DOI: 10.3389/fpls.2015.00138
|View full text |Cite
|
Sign up to set email alerts
|

Common reed accumulates starch in its stem by metabolic adaptation under Cd stress conditions

Abstract: In a previous study, we reported that the common reed accumulates water-soluble Cd complexed with an α-glucan-like molecule, and that the synthesis of this molecule is induced in the stem of the common reed under Cd stress. We studied the metabolic background to ensure α-glucan accumulation under the Cd stress conditions that generally inhibit photosynthesis. We found that the common reed maintained an adequate CO2 assimilation rate, tended to allocate more assimilated 11C to the stem, and accumulated starch g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…Interestingly, Barcelo et al [25] did not observe starch grains in the plastids of six-day-old Phaseolus vulgaris root after 15 days of 5 µg/mL CdCl 2 supplementation. However, similar to our results, Higuchi et al [47] observed starch accumulation under Cd stress, but in the stem of common reed. Moreover, since the export and allocation of carbon was not disturbed by Cd, these authors suggested that it might be an adaptive response, rather than a result of damage under excess Cd conditions [47,48].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Interestingly, Barcelo et al [25] did not observe starch grains in the plastids of six-day-old Phaseolus vulgaris root after 15 days of 5 µg/mL CdCl 2 supplementation. However, similar to our results, Higuchi et al [47] observed starch accumulation under Cd stress, but in the stem of common reed. Moreover, since the export and allocation of carbon was not disturbed by Cd, these authors suggested that it might be an adaptive response, rather than a result of damage under excess Cd conditions [47,48].…”
Section: Discussionsupporting
confidence: 92%
“…However, similar to our results, Higuchi et al [47] observed starch accumulation under Cd stress, but in the stem of common reed. Moreover, since the export and allocation of carbon was not disturbed by Cd, these authors suggested that it might be an adaptive response, rather than a result of damage under excess Cd conditions [47,48]. Another feature we observed in the Cd-stressed root cells was oil bodies.…”
Section: Discussionsupporting
confidence: 92%
“…The main DEGs were chloroplast development and the carbon cycle pathway in early rice growth and development. Sucrose and starch contents due to alterations of the allocation pattern of photosynthetic fixed carbon (Higuchi et al, 2015;Pilkington et al, 2015). Temporary starch exists in cells with photosynthetic capacity, synthesized in the chloroplast during the day, and degraded at night to provide carbon for non-photosynthetic metabolism (Lunn, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In general, reed (Phragmites spp.) is widely known as highly tolerant plant to a variety of environmental stresses such as heavy metals (Higuchi et al 2015). In particular, this plant species accumulates Cd dominantly in roots rather than shoots (Ali et al 2004;Stoltz and Greger 2002).…”
Section: Discussionmentioning
confidence: 99%